Analisis kaedah pengukuran untung (Al-Ribh) dari perspektif muamalat Islam - Mohamad, M.T.; Borhan, J.T.; Shuib, M.S.; Sulaiman, A.A. (2012)
Profit is a crucial element in business organizations or institutions involved in the business. Any institution or business organization will not survive if the goal of making profits is not emphasized or ignored. Article will discuss some theoretical profit from the point of definition, concept, theoretical development which includes several stages of writing. Article also discusses the theory of profit from Islamic perspective by reference to the various views and opinions of prominent scholars from their respective schools. This article also discusses the method of determining the rate of profit according to Islamic law based on the reference guidelines set by the scholars. Overall, it can be concluded that the concept of profit either in Islamic or conventional economics is always changing from time to time to meet the people's business goals. Only differences are in terms of profit generation method in which the Islamic economy, the resulting profit is based on Islamic rulings that finally brought to justice and economic prosperity.